Two-dimensional mapping method for evaluation of phase-locked loop signal in cryo-CMOS qubit control circuits - Matsuoka, Ryutaro; Wachi, Yusuke; Tsuchiya, Ryuta; Mizuno, Hiroyuki; Kodera, Tetsuo (Japanese Journal of Applied Physics, 2025)
Cryogenic control systems are essential for integrating semiconductor spin qubits, and reducing phase noise in phase-locked loop (PLL) frequency synthesizers is critical for high-fidelity spin qubit control. Conventional single-frequency phase noise evaluation methods are not suitable for the multi-frequency demands of spin qubit architectures. To address this, we develop a two-dimensional (2D) phase noise mapping method that evaluates spectral purity as a function of both output and offset frequency. Using a cryogenic fractional-N PLL, we measure phase noise under different reference frequencies and observe frequency dependence of spurious signal. Simulations based on these measurements show infidelity variations up to ∼0.08% across 19.60–20.40 GHz. Our method enables identification of optimal signal configurations and supports resource-efficient design of control electronics. This framework contributes to a practical tool for scaling spin qubit systems and improving signal quality in cryogenic quantum processors.